2011
DOI: 10.1093/gbe/evr028
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Mutation and Selection in Speciation: From Hugo de Vries to the Modern Genomic Era

Abstract: One of the most important problems in evolutionary biology is to understand how new species are generated in nature. In the past, it was difficult to study this problem because our lifetime is too short to observe the entire process of speciation. In recent years, however, molecular and genomic techniques have been developed for identifying and studying the genes involved in speciation. Using these techniques, many investigators have already obtained new findings. At present, however, the results obtained are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 127 publications
(152 reference statements)
0
59
1
2
Order By: Relevance
“…3 B) offers the classical framework to understand genic incompatibilities reducing hybrid fitness due to dysfunctional interactions among neutrally or adaptively accumulated alleles at one or several loci [Coyne and Orr, 2004]. Alternative models, such as the 'mutation-rescue model', may also explain genic incompatibilities, including nucleo-cytoplasmic interactions [reviewed in Nei and Nozawa, 2011].…”
Section: Genic Incompatibilities and Their Purgingmentioning
confidence: 99%
“…3 B) offers the classical framework to understand genic incompatibilities reducing hybrid fitness due to dysfunctional interactions among neutrally or adaptively accumulated alleles at one or several loci [Coyne and Orr, 2004]. Alternative models, such as the 'mutation-rescue model', may also explain genic incompatibilities, including nucleo-cytoplasmic interactions [reviewed in Nei and Nozawa, 2011].…”
Section: Genic Incompatibilities and Their Purgingmentioning
confidence: 99%
“…As noted earlier, his Oenothera mutants were shown to arise, via several different types of complex changes in chromosomes, from an original polyploid hybrid, rather than via ordinary gene mutation (Sturtevant, 2001). Nevertheless, it is now known that most plant species are ancestrally polyploid, and that the types of changes studied by de Vries are quantitatively important in plant speciation (Nei and Nozawa, 2011).…”
Section: Speciation and Incompatibilitymentioning
confidence: 99%
“…One of the re-discoverers of Mendel's laws in 1900, Hugo de Vries studied botany at the Leiden University in The Netherlands and is one of the pioneers who paved the way for modern evolutionary synthesis [1]. Since then mutation research has come a long way with many of the advances expertly reported on by the journal of that same name, Mutation Research, founded by the late Fritz Sobels in 1964.…”
Section: Editorialmentioning
confidence: 99%